Synthesis of metronidazole based thiazolidinone analogs as promising antiamoebic agents. Issue 23 (1st December 2020) - Ansari, Mohammad Fawad; Inam, Afreen; Ahmad, Kamal; Fatima, Shehnaz; Agarwal, Subhash M.; Azam, Amir
Graphical abstract: Abstract: Metronidazole and its derivatives are widely used for the treatment of amoebiasis. However, metronidazole is considered as the standard drug but it has many side effects. The present study describes the synthesis of a series of metronidazole based thiazolidinone analogs via Knoevenagel condensation of 4-[2-(2-methyl-5-nitro-1 H -imidazole-1-yl)ethoxy]benzaldehyde 1 with various thiazolidinone derivatives 2 –14 to get the new scaffold (15 –27 ) having better activity and lesser toxicity. Six compounds have shown better efficacy and lesser cytotoxicity than the standard drug metronidazole towards HM1: IMSS strain of Entamoeba histolytica . These compounds may combat the problem of drug resistance and might be effective in identifying potential alternatives for future drug discovery against Eh OASS.